SIGNIFICANCE OF PULSE PRESSURE AND MANAGEMENT STRATEGY OF THE PETIENTS WITH PERMANENT CARDIAC PACING - Pochinska, M. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2016)
Clinical importance of the pulse pressure (PP) in patients with permanent pacemaker (PM) is discussed in this review. Clinical characteristics, hemodynamic parameters, stimulation parameters, depending on the PP, and the ability to optimize medication with antihypertensive drugs are considered. Implanted pacemaker and CRT are changing the PP, which substantiates the need for additional medical supervision. PP is an independent predisposing and prognostic factor for cardiovascular complications and mortality, and therefore is being intensively studied. The implantation of pacemaker and CRT, solves the problem of bradysystolic arrhythmias and HF, and leads to regular changes in PP among the other hemodynamic parameters. The PP role and abilities of its optimization, including due to medical management of patients, is still not studied appropriately.